Nonpainful wide-area compression inhibits experimental pain. Issue 9 (September 2016) - Honigman, Liat; Bar-Bachar, Ofrit; Yarnitsky, David; Sprecher, Elliot; Granovsky, Yelena
Abstract : Abstract: Compression therapy, a well-recognized treatment for lymphoedema and venous disorders, pressurizes limbs and generates massive non-noxious afferent sensory barrages. The aim of this study was to study whether such afferent activity has an analgesic effect when applied on the lower limbs, hypothesizing that larger compression areas will induce stronger analgesic effects, and whether this effect correlates with conditioned pain modulation (CPM). Thirty young healthy subjects received painful heat and pressure stimuli (47°C for 30 seconds, forearm; 300 kPa for 15 seconds, wrist) before and during 3 compression protocols of either SMALL (up to ankles), MEDIUM (up to knees), or LARGE (up to hips) compression areas. Conditioned pain modulation (heat pain conditioned by noxious cold water) was tested before and after each compression protocol. The LARGE protocol induced more analgesia for heat than the SMALL protocol ( P < 0.001). The analgesic effect interacted with gender ( P = 0.015). The LARGE protocol was more efficient for females, whereas the MEDIUM protocol was more efficient for males. Pressure pain was reduced by all protocols ( P < 0.001) with no differences between protocols and no gender effect. Conditioned pain modulation was more efficient than the compression-induced analgesia. For the LARGE protocol, precompression CPM efficiency positively correlated with compression-induced analgesia. Large body area compression exerts an area-dependent analgesic effect on experimental pain stimuli. The observed correlation with pain inhibition in response to robust non-noxious sensory stimulation may suggest that compression therapy shares similar mechanisms with inhibitory pain modulation assessed through CPM. Abstract : Supplemental Digital Content is Available in the Text.Upper limb experimental heat pain is attenuated by lower limb nonpainful compression pants in an area-dependent mode, and in correlation with conditioned pain modulation, in healthy controls.